Identity and Foreign Policy: Canada as a Nation of the Americas. (30th May 2013) - Thérien, Jean‐Philippe; Mace, Gordon
ABSTRACT Using Canada's relations with the Americas as a case study, this article seeks to better understand the link between identity and foreign policy. It argues that there is a gap between the Canadian government's recent efforts to construct a state identity increasingly turned toward the Americas and Canadians' national identity as it is expressed through public opinion. It concludes that the most plausible explanation for this gap probably has to do with Canada's European cultural heritage. The analysis shows that the projection of national identity into foreign policy is a much more complex process than the projection of state identity.